2020
DOI: 10.1142/s0218127420501102
|View full text |Cite
|
Sign up to set email alerts
|

Input–Output Characterization of the Dynamical Properties of Circuits with a Memelement

Abstract: The paper proposes a novel input–output approach to characterize the dynamical properties of a class of circuits composed by a linear time-invariant two-terminal element coupled with one of the ideal memelements (memory elements) introduced by Prof. L. O. Chua, i.e. memristors, memcapacitors, and meminductors. The developed approach permits to readily determine the conditions under which the dynamics of any circuit of the class admits a first integral. It is also shown that the circuit dynamics can be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…Memristor circuit capable to reproduce the dynamics of the FitzHugh-Nagumo neuron model: the passive two-terminal elementi L (blue box) with Rm, Lm, and Cm as in (32), and the flux-controlled memristor (red box) with the nonlinear characteristic (30).…”
Section: A the Case Of Singular Matrix Amentioning
confidence: 99%
See 1 more Smart Citation
“…Memristor circuit capable to reproduce the dynamics of the FitzHugh-Nagumo neuron model: the passive two-terminal elementi L (blue box) with Rm, Lm, and Cm as in (32), and the flux-controlled memristor (red box) with the nonlinear characteristic (30).…”
Section: A the Case Of Singular Matrix Amentioning
confidence: 99%
“…For ideal memristors, it has been shown that multistability is connected to the fact that the state space of memristor circuits is decomposed into a continuum of invariant manifolds [11]. Since on each manifold either convergent or oscillatory and more complex behaviors can be displayed, the coexistence of infinitely many attractors is a natural scenario for circuits with ideal memristors [26], [27], [28], [29], [30], [31], [32]. Moreover, each invariant manifold can be uniquely identified via some parameters referred to as manifold indexes, whose values depend on the initial conditions of the circuit.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, structural changes of the attractors are observed when the initial conditions are varied while keeping constant the values of the circuit parameters, a peculiar phenomenon which is referred to as bifurcations without parameters (Corinto and Forti, 2017 ; Di Marco et al, 2018 ; Innocenti et al, 2019b ). In particular, Di Marco et al ( 2018 ), Innocenti et al ( 2019b ) have employed techniques within the Harmonic Balance (HB) context for predicting limit cycles and their bifurcations by first showing that the dynamics of the memristor circuit admits an equivalent input-output representation, which has been recently extended also to circuits containing memory elements (Innocenti et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, the flux-charge approach has been extended to much broader classes of circuits containing more than one memristor as well as memcapacitors and meminductors (see, e.g., [8,9,[36][37][38][39][40][41] and references therein). Finally, [42] provides a systematic input-output approach to characterize the dynamical properties of a class of circuits composed of a linear time-invariant two-terminal element coupled with one of the ideal mem-elements. Such an approach can be fruitfully used to predict limit cycles and their bifurcations via the Harmonic balance method (HBM) [43][44][45], as shown in [46,47].…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, the linear two-terminal element can contain linear R, L, C components and ideal operational amplifiers, while the mem-element can be a flux-or charge-controlled memristor, a flux-or σ -controlled capacitor, a ρor charge-controlled inductor. Then, on the basis of the approach developed in [42], it is shown that each circuit of the class admits a suitable feedback system representation. Exploiting the structural properties of such a representation, Sect.…”
Section: Introductionmentioning
confidence: 99%